Al-Taftāzānī’s Discussion on The Nature of Man Sine Qua Non (Essential) to The Mukallaf in The Science of Uṣūl Al-Fiqh - Ramli, Mohd Hilmi (Jurnal Fiqh, 2025)
The discussion of mukallaf as the maḥkūm ‘alayh is a key component in many works of uṣūl al-fiqh. As a mukallaf, a person must not only recognize his or her individual responsibility to fulfill duties and obligations to God but also meet two essential conditions: first, possessing intellect (‘aql) and second, having legal capacity (ahlīyyah). However, not all works of uṣūl al-fiqh explore the metaphysical underpinnings of the concept of mukallaf. This study aims to delve into al-Taftāzānī’s Talwīḥ ‘alā Tawḍīḥ, a synthesis work of uṣūl al-fiqh that articulates the metaphysical aspects of humanity that underpin the concept of mukallaf. The study will employ both textual and conceptual methods to understand the nature of man and its related concepts, particularly ‘aql and ahlīyyah. The study finds that al-Taftāzānī’s commentary, which reflects the views of notable jurists, making a great explanation on the insānī aspects of mukallaf.